The mineralogy and chemical properties of sedimentary waste rocks with carbon sequestration potential at the Selinsing gold mine, Pahang - Syed Hasan, Sharifah Nur Munirah; Mohd Kusin, Faradiella; Jusop, Shamsuddin; Mohamat Yusuff, Ferdius @ Ferdaus (Universiti Putra Malaysia Press, 2019)
Waste rocks are a non-economical by-product of mining operations, which can lock up carbon dioxide into a carbonate form and thereby help reduce greenhouse gases emissions. The aims of this research are to determine the mineral and chemical composition of the sedimentary waste rocks of gold mines and to classify the potential of silicate minerals to be a feedstock for carbonation mineralization. The sampling was undertaken at the Selinsing gold mine, where waste rocks were collected from the waste dump, stockpiles, the borrow pit, and the main pit. The mineralogical and chemical component of the sedimentary waste rocks were explored using X-ray diffraction and energy dispersive X-ray spectroscopy. The findings indicated that the presence of divalent cations, of 55.12% for CaO, 9.09% for MgO, and 16.24% for Fe2O3 from gold mine waste, capable of sequestering carbon dioxide into calcium, magnesium and iron carbonates, respectively, through carbonation of mineral. The domination of silicate minerals such as quartz, muscovite, kaolinite, chlorite, albite, and carbonate minerals such as calcite, have been found to be widespread in sedimentary waste rocks. However, the natural silicates (chlorite, muscovite) and carbonates (calcite) are potential minerals which can be consumed as feedstock for carbonation processes because they contain the magnesium, iron, and calcium elements which can form stable carbonates in the presence of carbon dioxide. The mineralogy and chemical composition of sedimentary waste rocks from the Selinsing gold mine provides a better understanding of the future carbonation reaction to sequester more carbon dioxide in response to climate change.